THE IMPLEMENTATION OF GENERIC SKILLS AT TECHNICAL SCHOOLS: COMPARATIVE ANALYSIS IN DIFFERENT PLATFORM - Esa, Ahmad; Mohd. Yunus, Jailani; Mat Assain @ Hashim, Fadilah (Journal of Techno-Social, 2011)
Mastering the soft skills is important among students nowadays but the most dominant embeded platform for this skill is still unidentified. The purpose of this research was to identify the most dominant platform to embed the soft skills to order to assist student to master it. This research determines the level of exposure in three different platforms which are in cocuriculum activities, workshop and class adopted a one. The research descriptive design where data the result of the study hence would show the most dominant platform had been collected by questionnaire and interview. The respondents for this questionnaire were 260 students from Sekolah Menengah Teknik Batu Pahat and Sekolah Menengah Teknik Kluang, Johor. The result of the research indicates that the class platform had the highest level of soft skills implementation with 3.75 min, followed by cocuriculum 3.70 min and finally in workshop 3.69 min. The next result of the research also showed that the most dominant in implementating soft skills are curriculum activities and workshop. This was evident as Paired Sample T-test had shown that there was no significant difference in the level of implementation between these two platform at the value sig.(2-tailed) 0.605. Sample T-test had shown that there was significant difference in the level of embeded between these three platforms. The platforms were cocurriculum, class and workshop platform at the value of sig. (2-tailed) and 0.002.